2021 Alzheimer's disease facts and figures (Alzheimer's & dementia, 2021)
This article describes the public health impact of Alzheimer's disease (AD), including incidence and prevalence, mortality and morbidity, use and costs of care, and the overall impact on caregivers and society. The Special Report discusses the challenges of providing equitable health care for people with dementia in the United States. An estimated 6.2 million Americans age 65 and older are living with Alzheimer's dementia today. This number could grow to 13.8 million by 2060 barring the development of medical breakthroughs to prevent, slow or cure AD. Official death certificates recorded 121,499 deaths from AD in 2019, the latest year for which data are available, making Alzheimer's the sixth‐leading cause of death in the United States and the fifth‐leading cause of death among Americans age 65 and older. Between 2000 and 2019, deaths from stroke, heart disease and HIV decreased, whereas reported deaths from AD increased more than 145%. This trajectory of deaths from AD was likely exacerbated in 2020 by the COVID‐19 pandemic. More than 11 million family members and other unpaid caregivers provided an estimated 15.3 billion hours of care to people with Alzheimer's or other dementias in 2020. These figures reflect a decline in the number of caregivers compared with a decade earlier, as well as an increase in the amount of care provided by each remaining caregiver. Unpaid dementia caregiving was valued at $256.7 billion in 2020. Its costs, however, extend to family caregivers’ increased risk for emotional distress and negative mental and physical health outcomes — costs that have been aggravated by COVID‐19. Average per‐person Medicare payments for services to beneficiaries age 65 and older with AD or other dementias are more than three times as great as payments for beneficiaries without these conditions, and Medicaid payments are more than 23 times as great. Total payments in 2021 for health care, long‐term care and hospice services for people age 65 and older with dementia are estimated to be $355 billion. Despite years of efforts to make health care more equitable in the United States, racial and ethnic disparities remain — both in terms of health disparities, which involve differences in the burden of illness, and health care disparities, which involve differences in the ability to use health care services. Blacks, Hispanics, Asian Americans and Native Americans continue to have a higher burden of illness and lower access to health care compared with Whites. Such disparities, which have become more apparent during COVID‐19, extend to dementia care. Surveys commissioned by the Alzheimer's Association recently shed new light on the role of discrimination in dementia care, the varying levels of trust between racial and ethnic groups in medical research, and the differences between groups in their levels of concern about and awareness of Alzheimer's disease. These findings emphasize the need to increase racial and ethnic diversity in both the dementia care workforce and in Alzheimer's clinical trials.